PENGARUH CONTENT MARKETING, INFLUENCER MARKETING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN SKINCARE WHITELAB DI KOTA BATAM - Legista Delona Guci; Winda Evyanto (Berajah Journal, 2026)
This study was conducted to determine the influence of content marketing, influencer marketing and online customer reviews on purchasing decisions for Whitelab skincare products in Batam, both individually and collectively. This study employed a quantitative method using multiple linear regression analysis. The sample consisted of 100 respondents, determined using Lemeshow’s formula, through purposive sampling and non-probability sampling methods. Data were collected by distributing questionnaires and subsequently analysed using SPSS software. The results of the study indicate that, when analysed partially, Content Marketing has a positive and significant effect on the Purchase Decision with a calculated t-value of 2.478 and a significance level of 0.015; Influencer Marketing has a positive and significant effect on the Purchase Decision with a calculated t-value of 5.890 and a significance level of <0.001; whilst Online Customer Reviews do not have a positive and significant effect on Purchase Decisions, with a t-value of 30.079 and a significance level of <0.001. The R-squared value of 0.485 indicates that these three variables collectively explain 48.5% of the variation in Purchase Decisions, whilst the adjusted R-squared value of 0.468 indicates that the remaining 53.2% is explained by other factors outside the scope of this research model.